Continental influence on the fertilization of marine waters during the late quaternary in the south of the Brazilian continental margin (Ocean and Coastal Research, 2022)
This study sought to understand the role of continental influence on ocean productivity along the late Quaternary based on the comparison between continental palynomorphs and paleoproductivity proxies from the marine sediment core SIS188. Retrieved from the slope of the Pelotas Basin at a depth of 1,514 m, the core documents the time interval between 47.8 and 7.4 cal ka BP, including the Marine Isotope Stages (MIS) 3, 2 and 1. The palynological content found in the core SIS188 indicates a typical flora of the southern Brazil highlands, which is at the same latitude as the core. Thus, continental input sources, such as wind-borne dust and discharges from the Mampituba and Araranguá rivers, would more likely account for the palynological content than the Brazilian Coastal Current (BCC). During the glacial intervals (MIS 3 and MIS 2), paleoproductivity (indicated by the proxies coccolith numbers, N Ratio, and TOC content) suggest the intensification of upwelling and transport of wind dust, the latter of which may have transported pollen grains to the core region. There is a concentration decrease of continental palynomorphs at the end of MIS 2, which is accentuated during MIS 1 when the sea level is higher. Paleoproductivity was high during MIS 1, especially from the Holocene onwards, although the concentration of continental-derived palynomorphs decreases sharply, showing that the rise in sea level interferes with the fertilization of marine waters far from the coast by continental input.